The roles of burnout, self-rated health, and teacher self-efficacy in fostering perceived teacher work ability - Petr Hlado; Libor Juhaňák; Klara Harvankova (Humanities & Social Sciences Communications)
Abstract Maintaining work ability is essential for meeting the job requirements of the teaching profession. The aim of the present study was to examine the relationships between perceived work ability, burnout, self-rated physical and mental health, and self-efficacy among teachers. This research was grounded in the job demands-resources (JD-R) model, providing a theoretical framework for exploration. A two-wave longitudinal study was conducted among Czech primary and lower secondary school teachers. Data were collected using web-based questionnaires at two-time points, 1 year apart. At Time 1, the sample comprised 853 participants (mean age: 45.9 years ± 10.8; mean years in the teaching profession: 19.4 years ± 12.1; 86.1% females). The findings highlight the crucial roles of burnout, self-rated mental health, and teacher self-efficacy in fostering perceived work ability among teachers. The mediation analysis revealed that self-rated mental health serves as mediator between burnout and perceived teacher work ability, while burnout mediates the relationship between teacher self-efficacy and perceived work ability. This study provides empirical support for the principles of the JD-R model within the teaching profession. Practical implications and future directions are discussed.